Studi Hubungan Deviden dan Earning Perusahaan - Werner R. Murhadi (Jurnal Manajemen Maranatha, 2009)
This research aimed to test “do the information contains on the dividends have an ability to predict the expected earning?” Our sample is all listed companies which distributed cash dividend during 2000-2005 at Jakarta Stock Exchange. We finally collected 544 observations and conducted generalized method of moments for analysis. The finding indicates that the dividends have positive influence to the company expected earning growth, furthermore, it supports the signaling theory, nonetheless refuses the dividend irrelevant theory and the disappearing dividend phenomenon.